ИСПОЛЬЗОВАНИЕ КОМПЬЮТЕРА В СОЗДАНИИ МУЗЫКИ - Абылова, Г.Ж. (SCIENCE and SOCIETY, 2017)
The article is devoted to the study of basic concepts of musical computer technologies the main possibilities of programmes and practical training. Methods of using a computer in the creation of music and musical works with the help of musical computer application program software and ACID 4.0 e Jay have also been studied in the article.
Keywords: computer; computer technologies; methods; stave editor; program; sample; sounds